ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTEGRITAS LAPORAN KEUANGAN DENGAN PROFITABILITAS DAN LEVERAGE SEBAGAI CONTROL VARIABEL (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA) - Parlindungan Parlindungan (Jurnal Telaah dan Riset Akuntansi, 2014)
The purpose of this study was to simultaneously and partially analyze the influence of institutional ownership, management ownership, independent commissioners and audit committee on the integrity of the financial statements with profitability, and leverage as control variables. The research design used was causal design. The population of this study was 30 bank companies registered in the Indonesia Stock Exchange from 2009 to 2012 and 24  companies with 108 analysis units were selected to be the samples for this study through purposive sampling technique.  The hypothesis of the data obtained were processed through multiple linear regression tests by busing SPSS program. The result of the hypothesis proved that simultaneously institutional ownership, management ownership, independent commissioners and audit committee had influence on the integrity of the financial statements. While audit committee in partial a positive and significant toward integrity of the financial statements. institutional ownership, management ownership, independent commissioners in partial a negative and not significant toward integrity of the financial statements. Prediction capability from these four variable toward integrity of the financial statements is 20,% where the balance 80% is affected to other factors which was not to be entered to research model.  Keywords: Institutional Ownership, Ownership Management, Audit Committee and Independent Commissioner, and The Integrity of Financial Statements.